In-between Wor(l)ds: female autofiction and postcolonial identity in Marie Cardinal´s Au pays de mes racines, Marguerite Duras´s L´amant and Isabela Figueiredo´s Caderno de Memórias Coloniais - Cominetti, Enrica Aurora (2019)
Female autofiction can be considered as a form of feminist confessional since, by challenging dominant configurations of knowledge – such as those embodied by autobiographism – and drawing attention to women’s personal issues, it aims at articulating the multiplicity of the female narrative subject. Autofictional works such as Marie Cardinal’s Au pays de mes racines [In the Country of my Roots], Marguerite Duras’s L’amant [The Lover] and Isabela Figueiredo’s Caderno de Memórias Coloniais [Notebook of Colonial Memories] can therefore be viewed as dealing with female personal concerns in a political way. This is because their exploration of women’s marginal status in formerly colonial countries like Algeria, Indochina and Mozambique, functions as an empowering tool through which they challenge the structures of domination impinging on their identity while asserting their own individuality. The purpose of this dissertation is to explore how the literary genre of autofiction harmonizes with and serves to better articulate issues of female subjectivity and cultural hybridization, particularly as concerns the power dynamics at stake in the narratives’ transcultural contexts. The focus will be on the fragmented sense of self imbuing these novels and which is directly related to the liminal status occupied by the narrators who are in-between different cultures. The final objective is to investigate how the notion of in-betweenness, which underlies both the genre of autofiction itself and the structure of the texts, can function as a feminist category of representation of women’s subjectivity and which defies oppressive social conventions related to patriarchal colonial patterns.